Novel adapted de-loading control strategy for PV generation participating in grid frequency regulation - Gangui Yan; Shuai Liang; Qi Jia; Yuru Cai (The Journal of Engineering, 2019)
Existence PV generation mostly operates under the Maximum Power Point Tracking (MPPT) mode and has no ability to increase or decrease active power, accordingly, PV generation does not participate in grid frequency regulation. Due to an increasing penetration of grid-connected PV generation, when a frequency contingency event occurs, grid may have neither enough inertia response nor governor support and frequency deviation may have a risk of exceeding the limit. Therefore, a novel adapted de-loading control strategy without MPPT for grid-connected inverters is proposed here. This control strategy provides a reserve power in PV system to meet the frequency control demand and an online output Active Power-Voltage Matching (APVM) technique, which is generated as a control flowchart, is implemented in this control strategy to make it possible to adjust PV output voltage performance matching different active power demand with different operation modes. The proposed control strategy of PVs is simulated using PSCAD/EMTDC Software. Results verify the correctness and effectiveness of the proposed adapted de-loading control strategy under several operating conditions.